2007
DOI: 10.1007/s00384-007-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, consequences, and risk factors for anastomotic dehiscence after colorectal surgery: a prospective monocentric study

Abstract: Three risk factors for anastomotic leak have been identified, one is patient-related (ASA score), one is disease-related (rectal location), the third being surgery-related (prolonged operative time). These factors should be considered in perioperative decision-making regarding defunctioning stoma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
274
13
41

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(342 citation statements)
references
References 32 publications
(39 reference statements)
14
274
13
41
Order By: Relevance
“…The reason for this non-inclusion is that operator selection is a potential risk of bias because difficult cases tended to be operated by experts and some of the relatively easy cases are done by trainees, particularly in this cohort. ASA-PS classification is a reported predictive factor of postoperative complications after major abdominal surgeries for colorectal and pancreatic disease [36][37][38]. ASA-PS class 2 defines ''a patient with mild systemic disease'' such as controlled hypertension, diabetes without systemic effects, and cigarette smoking without chronic obstructive pulmonary disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this non-inclusion is that operator selection is a potential risk of bias because difficult cases tended to be operated by experts and some of the relatively easy cases are done by trainees, particularly in this cohort. ASA-PS classification is a reported predictive factor of postoperative complications after major abdominal surgeries for colorectal and pancreatic disease [36][37][38]. ASA-PS class 2 defines ''a patient with mild systemic disease'' such as controlled hypertension, diabetes without systemic effects, and cigarette smoking without chronic obstructive pulmonary disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…4 With current screening and diagnostic methods, the interval between construction of the colorectal anastomosis and diagnosis of leakage varies between 6 and 13 days. [5][6][7] Several studies have suggested that delay of diagnosis of CAL is associated with higher mortality rates and that only early management improves clinical outcome. [8][9][10] Therefore, new screening methods allowing detection of CAL in the early postoperative phase are needed.…”
mentioning
confidence: 99%
“…Komen et al(2009) encontraram 8,7% de fístulas em 739 anastomoses colorretais, identificando o tempo cirúrgico prolongado e o índice de massa corporal (IMC) maior que 30 kg/m² como fatores de risco independentes para a ocorrência de fístulas 10 . Outros fatores de risco identificados são: presença de doença inflamatória intestinal, operações retais, risco cirúr-gico aumentado (classificação da ASA), hipoalbuminemia, perda sanguínea intraoperatória aumentada e hemotransfusão 8,9 .…”
Section: Sumário Dos Resultadosunclassified
“…Swanson et al (2003) A presença de comorbidades associadas à doença de base pode ser esperada na faixa etária mais acometida pelos tumores colorretais. Dentre as complicações decorrentes das operações colorretais, a deiscência e fístula anastomóticas costumam ser consideradas as mais graves [8][9][10] . A incidência das fístulas anastomóticas em 63 cirurgias colorretais envolvendo anastomoses foi de cinco casos (7,9%).…”
Section: Sumário Dos Resultadosunclassified
See 1 more Smart Citation